Pengaruh Sumber Belajar Terhadap Minat Belajar Bahasa Arab Peserta didik Kelas X Pondok Pesantren Al Munawwir Krapyak Yogyakarta - Syafira Risti Sinatrya; Tahir Wijaya; Madian; Taufik Hidayat (al-Ittijah : Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2023)
An essential role in a country is held by education in creating quality human resources. Learning resources are essential in education. Learning resources are utilized by students in the learning process by providing facilities separately. This study aims to determine whether there is a relationship between learning resources and interest in learning Arabic because the data needed is in the form of numbers. This study is a simple correlation study using primary data sources. The variables in this study, Likert scale questionnaires, were used. Knowing the interest in learning has extensively impacted students because someone will be interested in doing something he has. So that learning resources and learning interests are related to each other in supporting the success of the learning process.